SISTEM INFORMASI PENGOLAHAN DATA ASET PADA KANTOR DESA TALANG BABAT TANJUNG JABUNG TIMUR - Fery Purnama; Muda Aditama (JURNAL AKADEMIKA)
This study aims to build Data Processing Information Systems Assets Office Talang Babat Tanjung Jabung Timur, According to the Regulation No. 4 of 2007, the understanding of the management itself is a series of activities ranging from planning, procurement, use, utilization, security, maintenance, removal, alienation , administration, assessment, coaching, supervision and control. Village asset management carried out by the appropriate rules, that where such activities can be a land-use village treasury, and other activities mentioned in the Regulation No. 4 of 2007. In order to simplify and speed up data processing goods at the village office .. This system built using Delphi 7 Programming Languages and Ms. Access as the database as for data input is employee data, room data, and data assets. The input data to be processed in the process of inputting data. While the output of the asset data reports KANTOR DESA TALANG BABAT. The results showed with the construction of this information system, the data processing and reporting of data items becomes easier, faster and data recording errors can be avoided, so that the process of reporting to the head office of the village can be in accordance with the specified time.